A connection in life and death: The BCL-2 family coordinates mitochondrial network dynamics and stem cell fate - Rasmussen, Megan L. (Int Rev Cell Mol Biol, 2020)
The B cell CLL/lymphoma-2 (BCL-2) family of proteins control the mitochondrial pathway of apoptosis, also known as intrinsic apoptosis. Direct binding between members of the BCL-2 family regulates mitochondrial outer membrane permeabilization (MOMP) after an apoptotic insult. The ability of the cell to sense stress and translate it into a death signal has been a major theme of research for nearly three decades; however, other mechanisms by which the BCL-2 family coordinates cellular homeostasis beyond its role in initiating apoptosis are emerging. One developing area of research is understanding how the BCL-2 family of proteins regulate development using pluripotent stem cells as a model system. Understanding BCL-2 family-mediated regulation of mitochondrial homeostasis in cell death and beyond would uncover new facets of stem cell maintenance and differentiation potential.